Effectiveness of audit committees in achieving independence of internal audit: A case study of Tanzania Petroleum Development Corporation (TPDC) - Mkwe, Thomas V. (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment for the requirements for the award of the Degree of Master of Science in Accounting and Finance (MSc A & F) of Mzumbe University.